Torque Performance Analysis on Interior Permanent Magnet (IPM) Synchronous Motor Arrangement - Ros Husaini, Irshyad Syahmi; Aziz, Roziah (Evolution in Electrical and Electronic Engineering, 2024)
This study proposes designs of Interior Permanent Magnet Synchronous Motor (IPMSM) with different Interior Permanent Magnet (IPM) topology. The purpose of this study is to analyse and determine which IPM topology generate the highest torque. JMAG Desginer 18.1 software is used to construct a model of an 18-slots, 8-poles Permanent Magnet Synchronous Motor (PMSM) with five different variations of IPM topology. The proposed design incorporates many different IPM topologies, including U-shape, V-shape, UU-shape, VV-shape as well as UV-shape. The torque performance of the proposed design has been analysed by using software simulation. Based on the current finding, it is found that the double layer IPM arrangement produced higher torque rather than single layer IPM arrangement. Between single layer topologies, the V-shape topology was shown to have a greater amount of torque than the U-shape topology, while the VV-shape topology was found to have the highest torque of all the designs presented.